Perivascular Spaces, Glymphatic System and MR - Yu, Linya; Hu, Xiaofei; Li, Haitao; Zhao, Yilei (Frontiers in Neurology, 2022)
The importance of the perivascular space (PVS) as one of the imaging markers of cerebral small vessel disease (CSVD) has been widely appreciated by the neuroradiologists. The PVS surrounds the small blood vessels in the brain and has a signal consistent with the cerebrospinal fluid (CSF) on MR. In a variety of physio-pathological statuses, the PVS may expand. The discovery of the cerebral glymphatic system has provided a revolutionary perspective to elucidate its pathophysiological mechanisms. Research on the function and pathogenesis of this system has become a prevalent topic among neuroradiologists. It is now believed that this system carries out the similar functions as the lymphatic system in other parts of the body and plays an important role in the removal of metabolic waste and the maintenance of homeostatic fluid circulation in the brain. In this article, we will briefly describe the composition of the cerebral glymphatic system, the influencing factors, the MR manifestations of the PVS and the related imaging technological advances. The aim of this research is to provide a reference for future clinical studies of the PVS and glymphatic system.